2004
DOI: 10.1021/jo049824f
|View full text |Cite
|
Sign up to set email alerts
|

Unambiguous Detection of Target DNAs by Excimer−Monomer Switching Molecular Beacons

Abstract: A new class of molecular beacons were developed in which pyrene fluorophores were connected both at 3' and 5' ends of a single-stranded oligonucleotide. The two pyrene-based fluorophores were synthesized from the same starting material, so that the preparation of the beacons was simplified. The detection strategy of the beacons for target DNAs is based on "excimer-monomer emission switching" of the pyrene fluorophores: excimer emission of the pyrene moieties changed to monomer one when the beacons hybridized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
109
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(111 citation statements)
references
References 33 publications
0
109
0
2
Order By: Relevance
“…Some spatially sensitive fluorescent dyes, such as pyrene (13)(14)(15)(16) and BODIPY Fl (17,18), can form excimers upon close encounter of an excited-state molecule with another ground-state molecule. The excimer emits at a longer wavelength than a monomer does.…”
Section: Design and Synthesis Of Light-switching Excimer Aptamer Probementioning
confidence: 99%
See 2 more Smart Citations
“…Some spatially sensitive fluorescent dyes, such as pyrene (13)(14)(15)(16) and BODIPY Fl (17,18), can form excimers upon close encounter of an excited-state molecule with another ground-state molecule. The excimer emits at a longer wavelength than a monomer does.…”
Section: Design and Synthesis Of Light-switching Excimer Aptamer Probementioning
confidence: 99%
“…For labeling oligonucleotide with pyrene, several methods were reported (13,24). Unfortunately, for dually labeling pyrene on both nucleic acid termini, the reported procedures proceeded in low yields partially because of incompatible solubility of the pyrene derivatives and nucleic acids.…”
Section: Design and Synthesis Of Light-switching Excimer Aptamer Probementioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31][32][33][34][35] The pyrene molecules in proximity generate uorescence peaks different from those of separated pyrenes. The combination of the aptamer and pyrene excimer provides an aptamer excimer probe for rapid detection of targets based on target-binding induced structure switching of the aptamer.…”
Section: Introductionmentioning
confidence: 99%
“…Fujimoto et al reported the detection of target DNAs by excimer-monomer switching of pyrene using the fluorescence resonance energy transfer (FRET) process [26]. A DNAbased nanomachine was reported by Liu et al using the FRET phenomenon [20].…”
Section: Introductionmentioning
confidence: 99%